The Development of Learning Video Media Based Geogebra for Increasing the Students' Mathematical Understanding (Journal of Informatics and Mathematical Sciences, 2017)
This research aimed to produce learning video media based on GeoGebra has been valid, practical, and effective. This development used ASSURE model development design. This research was conducted in Vocational High School Farmasi IKASARI Pekanbaru. The subject of the research are 2 people as the experts of instructional content and 2 people as  the experts of instructional media, 6 students for try out of small group, and 73 students for try out of large group devided by two class, those are an experiment class and a control class. The form of data collection instrumenst are questionnaires of the validity by expert, questionnaires of the practicality and writing test by the students. Data of questionnares were analyzed with descriptive statistics. Data of test were analyzed with inferensial statistics. The result showed that the evaluation of learning video media by the expert of instructional content is valid with verygood classification (94,167%), the evaluation of learning video media by the expert of instructional media is valid with verygood classification (94,615%). The practicality of learning video media by  students is practical with verygood classification (90,037%), and  learning video media is effective because there was significant different between posttest mean score data of experiment class 42,143 is bigger than posttest mean score data of control class 33,763. These result indicate  that the learning video media based on GeoGebra has been valid, practical, and effective.
Keywords: Learning Video Media; GeoGebra; Mathematical Understanding